(untitled) (Research, Society and Development, 2022)
Most human activities generate some kind of environmental impact on the environment, and with regard to necropolises it is no different. Besides the potential risk of groundwater and soil contamination, the solid waste generated during the activities, which range from burial and exhumation to visitation activities and religious practices, are also an important aspect to be considered. The objective of this work was to verify how the management of solid waste is performed in the São João Batista and São Francisco necropolis, two horizontal cemeteries located in Manaus, through a field visit. A brief literature review on environmental management in cemeteries was also performed. The results indicate that despite the low activity of the cemeteries the solid waste is not cared for differently from what is done with household waste. Several types of waste were found, mainly from construction and plastics used by visitors.